YM155, a survivin suppressant, triggers PARP-dependent cell death (parthanatos) and inhibits esophageal squamous-cell carcinoma xenografts in mice - Zhao, Nan (Oncotarget, 2015)
Here we demonstrated that sepantronium bromide (YM155), a survivin suppressant, inhibited esophageal squamous-cell carcinoma (ESCC) growth in mice bearing human ESCC xenografts without affecting body weight. In cell culture, YM155 decreased survivin levels and caused PARP-1 activation, poly-ADP polymer formation, and AIF translocation from the cytosol to the nucleus. Genetic knockdown of PARP-1 or AIF abrogated YM155-induced parthanatos cell death. Furthermore, FOS, JUN and c-MYC gene transcription, which is stimulated by activated PARP-1, was increased following YM155 treatment. Our data demonstrate that YM155 did not trigger apoptosis, but induced parthanatos, a cell death dependent on PARP-1 hyper-activation, and support clinical development of YM155 in ESCC.